Parental morph combination does not influence innate immune function in nestlings of a colour-polymorphic African raptor - Carina Nebel (Nature Portfolio, 2021)
Abstract Conditions experienced during early life can have long-term individual consequences by influencing dispersal, survival, recruitment and productivity. Resource allocation during development can have strong carry-over effects onto these key parameters and is directly determined by the quality of parental care. In the black sparrowhawk (Accipiter melanoleucus), a colour-polymorphic raptor, parental morphs influence nestling somatic growth and survival, with pairs consisting of different colour morphs (‘mixed-morph pairs’) producing offspring with lower body mass indices, but higher local apparent survival rates. Resource allocation theory could explain this relationship, with nestlings of mixed-morph pairs trading off a more effective innate immune system against somatic growth. We quantified several innate immune parameters of nestlings (hemagglutination, hemolysis, bacteria-killing capacity and haptoglobin concentration) and triggered an immune response by injecting lipopolysaccharides. Although we found that nestlings with lower body mass index had higher local survival rates, we found no support for the proposed hypothesis: neither baseline immune function nor the induced immune response of nestlings was associated with parental morph combination. Our results suggest that these immune parameters are unlikely to be involved in providing a selective advantage for the different colour morphs’ offspring, and thus innate immunity does not appear to be traded off against a greater allocation of resources to somatic growth. Alternative hypotheses explaining the mechanism of a low nestling body mass index leading to subsequent higher local survival could be related to the post-fledgling dependency period or differences in dispersal patterns for the offspring from different morph combinations.